Handgrip Strength as a Darwinian Fitness Indicator in Men - Gallup, Andrew C.; Fink, Bernhard (Frontiers in Psychology, 2018)
Handgrip strength (HGS) is a robust measure of overall muscular strength and function, and has long been predictive of a multitude of health factors and physical outcomes for both men and women. The fact that HGS represents such a ubiquitous measure of health and vitality may reflect the significance of this trait during human evolution. However, HGS is highly sexually dimorphic due to influences of androgenic hormones and fat-free body mass, suggesting that this trait has been further elaborated through sexual selection. Consistent with this view, research within evolutionary psychology and related fields has documented distinct relationships between HGS and measures of social and sexual behavior, especially in men. Here, we review studies across different societies and cultural contexts showing that male HGS predicts measures of aggression and social dominance, perceived formidability, male-typical body morphology and movement, courtship display, physical attractiveness, and sexual behavior and reproductive fitness. These findings underscore the value of including HGS as an independent measure within studies examining human sexual selection, and corroborate existing research suggesting that specific features of physical strength have and continue to be under positive directional selection in men.